2020
DOI: 10.1371/journal.pntd.0007843
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial activity of Urtica dioica extract against zoonotic cutaneous leishmaniasis

Abstract: BackgroundNeglected parasitic diseases (NTDs) like cutaneous leishmaniasis (CL) have caused high mortality and morbidity rate in developing countries. This disease is considered as one of the six major tropical diseases, and has a great importance in HIV infected individuals as an opportunistic infection in those areas that both infections are endemic. This study evaluated the therapeutic effects of the Urtica dioica L (U. dioica) aqueous extract as an anti-leishmanial herbal drug in-vitro and in-vivo, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 63 publications
2
36
0
3
Order By: Relevance
“…The aqueous extract of U. dioica halted the growth of L. major promastigotes with IC 50 of 4500 μg/mL. 15 …”
Section: Discussionmentioning
confidence: 96%
“…The aqueous extract of U. dioica halted the growth of L. major promastigotes with IC 50 of 4500 μg/mL. 15 …”
Section: Discussionmentioning
confidence: 96%
“…The possible mechanism of action is via modulation of the immune response. It did not show toxicity in macrophages 62 .…”
Section: Alternative Treatmentsmentioning
confidence: 89%
“…Badirzadeh reported that U. dioica extracts present promising antiparasitic activity and can be considered as an effective and harmless herbal material [44]. Sura et al [45] investigated the antimicrobial activities of aquatic extracts of U. dioica by disk diffusionmethod.…”
Section: Discussionmentioning
confidence: 99%